Rhetorical Moves and Metadiscourse in Nigerian Cooperative Annual Reports: A Comparative Analysis of Conventional and Shariah-Compliant Societies (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examines rhetorical move structures and metadiscourse features in annual reports from four Nigerian cooperative societies, two conventional (CoopEast/Shell East Staff MCS; Mosimi Staff MCS) and two Shariah-compliant (White Crescent MCS; Equity Trust MCS), comprising approximately 4,470 words of narrative prose. Using a qualitative comparative case study design integrating Swalesian genre analysis and Hyland’s metadiscourse model, the study identified a provisional seven-move structure (salutation, performance review, identity/values statement, challenges, future outlook, call to action, and gratitude/closing) across the corpus. Move 3, an explicit organisational identity and values statement, appeared consistently in both Shariah-compliant reports but not in conventional reports, suggesting a genre-differentiating feature warranting large-corpus verification. Metadiscourse analysis of 536 coded items revealed that conventional cooperatives use more boosters (8.9 vs. 4.7 per 1,000 words) and engagement markers (10.1 vs. 5.0), while Shariah-compliant cooperatives deploy more attitude markers (18.0 vs. 10.1) and hedges (16.9 vs. 11.8). These patterns reflect contrasting institutional ideologies: managerial confidence and member mobilisation in conventional reports versus ethical evaluation and religious humility in Shariah reports. The study contributes an empirically grounded, integrated framework for analysing cooperative institutional discourse and discusses practical implications for cooperative governance, member communication, and annual reporting policy in Nigeria.
Keywords: genre analysis; metadiscourse; cooperative annual reports; Shariah-compliant cooperatives; Nigeria